The Interference of Introversion–Extraversion and Depressive Symptomatology with Reasoning Performance: A Behavioural Study - Papageorgiou, Charalabos; Rabavilas, Andreas D.; Stachtea, Xanthy; Giannakakis, Giorgos A.; Kyprianou, Miltiades; Papadimitriou, George N.; Stefanis, Costas N. (Journal of psycholinguistic research, 2012)
The objective of this study was to investigate the link between the Eysenck Personality Questionnaire (EPQ) scores and depressive symptomatology with reasoning performance induced by a task including valid and invalid Aristotelian syllogisms. The EPQ and the Zung Depressive Scale (ZDS) were completed by 48 healthy subjects (27 male, 21 female) aged 33.5 ± 9.0 years. Additionally, the subjects engaged into two reasoning tasks (valid vs. invalid syllogisms). Analysis showed that the judgment of invalid syllogisms is a more difficult task than of valid judgments (65.1% vs. 74.6% of correct judgments respectively, p < 0.01). In both conditions, the subjects’ degree of confidence is significantly higher when they make a correct judgment than when they make an incorrect judgment (83.8 ± 11.2 vs. 75.3 ± 17.3, p < 0.01). Subjects with extraversion as measured by EPQ and high sexual desire as rated by the relative ZDS subscale are more prone to make incorrect judgments in the valid syllogisms, while, at the same time, they are more confident in their responses. The effects of extraversion/introversion and sexual desire on the outcome measures of the valid condition are not commutative but additive. These findings indicate that extraversion/introversion and sexual desire variations may have a detrimental effect in the reasoning performance.